Exploring Neuropsychiatric Symptom in Post-therapy Thyroid Disorder Patients: Anxiety Level Assessment - Naznin, Afroza; Yasmin, Farida; Sharmin, Samira; Rahman, Hosne Ara (Bangladesh Journal of Nuclear Medicine, 2024)
Thyroid disorders often present with an array of cognitive impairment symptoms, including dysphoria, depression, anxiety, psychosis, and apathy. While most of these problems do not impose any severe physical risk, they nonetheless significantly reduce quality of life and wellbeing. Moreover, some symptoms, like anxiety, tend to persist even after the restoration of biochemical euthyroid status. Hence, this study was designed to evaluate the level of anxiety with a structured questionnaire (the Hamilton Anxiety Rating Scale) in post-therapy thyroid carcinoma as well as hyperthyroidism patients. Study findings implied that most of the post-therapy patients experience only a low level of residual anxiety symptoms, which are unrelated to their initial diagnosis and biochemical thyroid status. Bangladesh J. Nuclear Med. 26(2): 110-114, 2023